Association between the risk of alcohol use and unprotected sex in adolescents in a city in the southern region of Brazil - Dallo, Luana; Martins, Raul Aragao [UNESP] (Abrasco, 2018)
This paper aims to analyze alcohol abuse and unprotected sex and the association between them in students in a city in the southern region of Brazil. This is a cross-sectional study using a quantitative approach with 590 secondary school students from two public schools. Regarding alcohol use, 14% scored from eight to 40 in The Alcohol Use Disorders Identification Test (AUDIT), which means, at least, a risky drinking behavior, with higher rate among boys. Moreover, 31.1% indulged themselves in binge drinking, which means drinking six or more doses according to AUDIT; and even among those who are low-risk drinkers, 21.1% had this drinking pattern. Regarding sexual behavior, young boys started sexual life earlier and the kind of relationship more referred to by them is one with no commitment; boys have uncommitted relationships, while girls have more relationships with commitment. In relation to the results of the association between alcohol use and sexual intercourse, 47.3% stated alcohol use before having sex, and those who started sexual activity got more drunk and had higher scores in the AUDIT. New studies are recommended regarding the association between both behaviors in Brazil, considering that the causal relationship is not clear and shows several explanation models.
Keywords: Adolescent; Sexual behavior; Alcoholism; Risk-taking; Sexuality